2021
DOI: 10.14710/dimj.v2i1.9667
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality among HIV/AIDS Patients

Abstract: Background: Morbidity and mortality of HIV/AIDS infections is still high and as  a global health problem particularly in Low-Middle Income Countries (LMICs). Indonesia ranks third in Asia Pacific in increasing HIV infection. A Study on risk factors for mortality in HIV/AIDS patients in Dr. Kariadi General Hospital has never been conducted. This study analyzed the risk factors for mortality among HIV/AIDS patients.Methods: Case control study, data from medical records of inpatients and outpatients in Dr. Kariad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Previous studies reported that patient's age was found to be predictor of mortality, where most of patients in older age were more likely to die [18,21,24]. Our study also revealed similar outcome.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies reported that patient's age was found to be predictor of mortality, where most of patients in older age were more likely to die [18,21,24]. Our study also revealed similar outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Majority of previous studies in Ethiopia also found twice or more risk of mortality for patients with lower CD4 count compared to those with a CD4 count of > 350 cells/ml [11,15,[19][20][21][22][23]. Studies performed across many parts of Africa and Asia reported that low level of CD4 count at baseline was associated with high level of mortality among patients on ART [16,18,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, 420.994 instances of TB were reported, with 1.85% of them infected with HIV [7]. TB is the second most common opportunistic illness in Indonesia, and it is also the leading cause of death among HIV patients [8]. Early detection of TB infection in HIV patients, on the other hand, can aid with efficient treatment and thereby reduce the mortality rate in HIV patients due to co-infection with TB.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually trauma, embolization or hemoglobinopathy consequence (Mustafa et al 2015). Immunodeficiency is HIV virus risk factor impact (Haider et al 2019, Kusumaadhi et al 2021. Splenic abscess is a rare case.…”
Section: Introductionmentioning
confidence: 99%